Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Lucille M. Gaffney, December 29, 1987 - Gaffney, Lucille M.et al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Swaledale contributed by Lucille M. Gaffney, December 29, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed